2018
DOI: 10.1021/acs.iecr.8b04453
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxymonosulfate by Fe3O4–CsxWO3/NiAl Layered Double Hydroxide Composites for the Degradation of 2,4-Dichlorophenoxyacetic Acid

Abstract: Novel Fe3O4–Cs x WO3/NiAl layered double hydroxide composites (FCW/LDH) for the activation of peroxymonosulfate (PMS) and the succeeding degradation of 2,4-dichlorophenoxyacetic acid (2,4-D) was synthesized through a simple method. The composites prepared were characterized by XRD, SEM, EDS, FT-IR, UV–vis DRS, and N2 physisorption, respectively. It was found that FCW/LDH could effectively catalyze PMS to generate sulfate radicals (SO4 •–) to degrade 2,4-D. The added 2,4-D (20 mg/L) was almost completely remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…The WO 3−x /Ag/ZnCr-LDH ternary heterostructure displayed excellent performance of TC degradation, which was attributed to the rapid separation efficiency of charge carriers through the Zscheme system. Furthermore, the oxygen deficiency of In addition, the high reusability and stability of the photocatalysts can still be maintained after four circulation runs [126]. The mechanism of improved peroxymonosulfate (PMS) activation with Fe 3 O 4 -Cs x WO 3 /NiAl-LDH heterojunction is demonstrated in Figure 13.…”
Section: Antibiotics and Pesticidesmentioning
confidence: 99%
“…The WO 3−x /Ag/ZnCr-LDH ternary heterostructure displayed excellent performance of TC degradation, which was attributed to the rapid separation efficiency of charge carriers through the Zscheme system. Furthermore, the oxygen deficiency of In addition, the high reusability and stability of the photocatalysts can still be maintained after four circulation runs [126]. The mechanism of improved peroxymonosulfate (PMS) activation with Fe 3 O 4 -Cs x WO 3 /NiAl-LDH heterojunction is demonstrated in Figure 13.…”
Section: Antibiotics and Pesticidesmentioning
confidence: 99%
“…Exploiting the photocatalysts with excellent photocatalytic degradation performance, which can be coated on the surface of polymer-based membranes is an option worth considering to solve the abovementioned difficulties. , Among these photocatalysts, nickel–aluminum-layered double hydroxide (NiAl-LDH), a typical 2D anionic layered material, has revealed extensive applications because of its chemical stability and being inexpensive. , However, it has been reported that NiAl-LDH could cause photocatalytic H 2 evolution, CO 2 reduction, mounts of organic wastewater degradation, , and so forth. However, its lower photocatalytic efficiency, which was due to the fast recombination of photogenic electron and hole pairs, has puzzled many scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need for the development of an efficient and cost-effective adsorbent for removing 2,4-D from water (Feng et al, 2008). Removal of the 2,4 -D is commonly reported using [Cu-Fe-NO 3 ] LDH or [Mg-Zn-Al] LDH as adsorbent material (Nejati et al, 2013;Zhao et al, 2018;Zhang et al, 2018) or using other intercalation methodologies such as: anion exchange of a precursor LDH, direct synthesis by co-precipitation, rehydration of a calcined LDH precursor and thermal reaction (Newman and Jones, 1998). So, in this work, [Co-Al-Cl] LDH, commonly used as electrodes in supercapacitors (Pourfarzad et al, 2019;Gao et al, 2018;Li et al, 2017a,b;Qiu and Villemure, 1997), was synthesized by the co-precipitation method at constant pH and tested as adsorbent for the removal of 2,4-D from contaminated waters.…”
Section: Introductionmentioning
confidence: 99%